ANALISIS KEBUTUHAN DIKLAT UNTUK KEDIKLATAN TENTANG MITIGASI TSUNAMI MELALUI PENDEKATAN KUANTITATIF DATA KUISIONER - Fiati Nurmaya; Aperta Ledy Alam (PPSDM Geominerba, 2020)
In training cycle activity, Training Need Analysis (TNA) is one part of the cycle which is before design of training. The methodology of TNA can be done in various way. One of TNA methodology is using the questionnaire instrument. The purpose of TNA with tsunami mitigation topic is to find competency gap from respondents which is come from 3 (three) units are Centre of Geological Survey, Centre of Volcanology and Geological Disaster Mitigation, and Centre of Marine Geology Research and Development, and involved 15 respondents. The result of TNA activity is competency gap that found in 5 (five) competencies which is contained in tsunami mitigation activity. The output of product will be using to design trainings with tsunami mitigation topics.